2015
DOI: 10.3389/fpsyg.2015.00829
|View full text |Cite
|
Sign up to set email alerts
|

Categorical perception of lexical tones in mandarin-speaking congenital amusics

Abstract: Previous research suggests that within Mandarin-speaking congenital amusics, only a subgroup has behavioral lexical tone perception impairments (tone agnosia), whereas the rest of amusics do not. The purpose of the current study was to investigate the categorical nature of lexical tone perception in Mandarin-speaking amusics with and without behavioral lexical tone deficits. Three groups of listeners (controls, pure amusics, and amusics with tone agnosia) participated in tone identification and discrimination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 27 publications
(59 reference statements)
4
24
0
Order By: Relevance
“…To calculate the category boundary and the slope of the identification curve, we fitted a logistic regression model on the tone identification function on an individual subject basis, consistent with prior work [59, 69], with the following formula: y=1/(1+exp(-b(x-c)))…”
Section: Star Methodsmentioning
confidence: 99%
“…To calculate the category boundary and the slope of the identification curve, we fitted a logistic regression model on the tone identification function on an individual subject basis, consistent with prior work [59, 69], with the following formula: y=1/(1+exp(-b(x-c)))…”
Section: Star Methodsmentioning
confidence: 99%
“…For instance, Nan et al (2010) found that Mandarin-speaking amusics performed worse than musically intact controls in the identification and discrimination of Mandarin tones, though there was individual variation in the severity of lexical tone impairment. Furthermore, there is some evidence that the deficiency in tonal language speakers is not confined to auditory pitch processing, but prevails to higher-level phonological processing, impeding the categorical perception of lexical tone (Jiang et al 2012b; Huang et al 2015a). All these findings suggest that the musical pitch deficit prevails to pitch processing in language.…”
Section: Introductionmentioning
confidence: 99%
“…While the aforementioned studies consistently pointed out that the impoverished lexical tone perception in tonal and nontonal language speakers with amusia is due to the domaingeneral pitch deficit, some studies have suggested that highlevel phonological processing of lexical tones might be impaired in native tonal language speakers with amusia. For instance, several studies provided evidence that categorical perception of native tones in tonal language speakers with amusia is impaired [19]- [21]. In contrast to the controls, Mandarin-speaking amusics showed no benefit for betweencategory tone discriminations, suggesting the absence or impairment of categorical perception of lexical tones, though one study found subgroup differences among Mandarinspeaking amusics [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several studies provided evidence that categorical perception of native tones in tonal language speakers with amusia is impaired [19]- [21]. In contrast to the controls, Mandarin-speaking amusics showed no benefit for betweencategory tone discriminations, suggesting the absence or impairment of categorical perception of lexical tones, though one study found subgroup differences among Mandarinspeaking amusics [18], [19]. In another study, Zhang et al found that Cantonese-speaking amusics exhibited less benefit in between-category discriminations than controls in speech contexts (lexical tone and vowel), suggesting reduced categorical perception; on the other hand, they performed inferiorly compared to controls regardless of between-and within-category discriminations in nonspeech contexts (pure tone), suggesting impaired auditory pitch processing [21].…”
Section: Introductionmentioning
confidence: 99%